Pengaruh Biaya Pemeliharaan Intensif terhadap Keuntungan Ayam Pedaging di Kabupaten Nagan Raya - Tria Widiawati; Said Mahdani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Livestock cultivation aims to meet the needs of animal food and improve the standard of living of farmers. Some of the factors that need to be considered in livestock cultivation include the selection of superior seeds, feed management, disease prevention and treatment, cages that meet standards, and marketing of livestock products. Livestock is one of the five agricultural subsectors where livestock is a cultivation or maintenance activity with the aim of benefiting from these activities. This study uses a type of quantitative research. The variables studied consisted of intensive maintenance costs and broiler profits. The population used in this study is all breeders in Nagan Raya Regency, each farm has different abilities and number of livestock. Therefore, the population used is all farmers with an intensive maintenance system in 5 sub-districts of Nagan Raya Regency, namely 12 chicken farmers. Because of the small number of populations, the sample in this study is the entire population. The data sources in this study consist of primary data and secondary data. In this study, quantitative analysis uses the Statistical Product and Service Solution (SPSS) version 26 computer program, because with this program analysis can be carried out quickly, and produce more accurate outputs. And the data analysis model used in this study is a simple linear regression method. The results of this study are that intensive maintenance costs incurred by broiler farmers have a very good influence on increasing profits from farmers' crops. Because with an intensive system the growth of chickens is more uniform and the deaths that occur in broilers can be avoided.